The Canadian horror film : terror of the soul - Loiselle, André, 1963-; Freitag, Gina, 1985- (University of Toronto Press, 2015)
Featuring chapters on Pontypool, Ginger Snaps, 1970s slasher films, Quebec horror, and the work of David Cronenberg, among many others, The Canadian Horror Film unearths the terrors hidden in the recesses of the Canadian psyche.